2008
DOI: 10.1002/yea.1615
|View full text |Cite
|
Sign up to set email alerts
|

New interacting partners of the F‐box protein Ufo1 of yeast

Abstract: The yeast F-box protein Ufo1 recruits proteins for ubiquitylation by the SCF ubiquitin ligase complex preparing them for proteasomal degradation. Ufo1 has a role in maintenance of genome stability; its substrates include Ho endonuclease and Rad30 polymerase of error-prone DNA repair. Ufo1 is an unusual F-box protein, as it has three ubiquitin interacting motifs (UIMs). Deletion of the genomic UIMs is lethal; ectopic expression of UFO1 UIMs extends protein half-life and arrests the cell cycle. A whole-genome st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Next morning the cells were diluted to A 600  = 0.1 and regrown to A 600  = 0.5 for TCA precipitation [77] and Western blotting [78].…”
Section: Methodsmentioning
confidence: 99%
“…Next morning the cells were diluted to A 600  = 0.1 and regrown to A 600  = 0.5 for TCA precipitation [77] and Western blotting [78].…”
Section: Methodsmentioning
confidence: 99%
“…Notably, Ubc4/5 work with SUMO-targeted ubiquitin ligases (STUbLs) that target poly-SUMOylated substrates (Sriramachandran and Dohmen, 2014;Uzunova et al, 2007). SUMO also modified five ubiquitin E3 ligases, Ubr1, Ufo1, Uls1, Gid7 and Ufd4, involved in a variety processes including the N-end rule, catabolite-degradation of fructose-1,6-bisphosphatase, transcription, cell cycle and genome maintenance (Bao et al, 2015;Baranes-Bachar et al, 2008;Finley et al, 2012;Kramarz et al, 2017;Lin et al, 2015;Sriramachandran and Dohmen, 2014;Varshavsky, 1997). Notable is Uls1, a putative STUbL that is thought to compete with a second STUbL, Slx5-Slx8, to displace from DNA poly-SUMOylated proteins that have been rendered defective or inactive (Sriramachandran and Dohmen, 2014;Tan et al, 2013;Wei et al, 2017).…”
Section: Ups Targets Included Ubc4 and Ubc5mentioning
confidence: 99%
“…Ho endonuclease is recruited by Ufo1 to the SCF ubiquitin ligase complex for ubiquitination and subsequently transferred by Ddi1 to the 26S proteasome for degradation (Kaplun et al, 2003; Kaplun et al, 2000). Ufo1 is a unique F-box protein, which in addition to the F-box and a protein-protein interaction domain contains three u biquitin- i nteracting m otifs (UIM) that are important for Ufo1 autoubiquitination (Baranes-Bachar et al, 2008). Interestingly, it was suggested that turnover of Ufo1 depends on the presence of Ufo1UIMs and the UBL domain of Ddi1 (Ivantsiv et al, 2006).…”
Section: Introductionmentioning
confidence: 99%